2004
DOI: 10.1002/ijc.20600
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinoma in Algiers, Algeria: Human papillomavirus and lifestyle risk factors

Abstract: We conducted a hospital-based case-control study in Algiers, Algeria. A total of 198 cervical carcinoma (CC) cases (including 15 adeno-and adenosquamous carcinomas) and 202 age-matched control women were included. Human papillomavirus (HPV) DNA in cervical cells was evaluated using a PCR assay. Odds ratios and corresponding confidence intervals were computed by means of unconditional multiple logistic regression models. HPV infection was detected in 97.7% of CC cases and 12.4% of control women (OR ‫؍‬ 635). Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 19 publications
12
45
1
5
Order By: Relevance
“…13 Certain characteristics associated with HPV positivity in this study coincide with the known risk factors for cervical cancer found in the INSP/IARC case-control study, 13 namely being separated or divorced, being in a polygamous marriage and reporting of husband's extramarital sexual relationships. Nulliparity, which is a protective factor for ICC, was associated with being HPV positive in the present and in previous IARC HPV Prevalence Surveys, 18 but this association is likely to be confounded by unmeasured sexual behaviour.…”
Section: Short Reportsupporting
confidence: 74%
See 1 more Smart Citation
“…13 Certain characteristics associated with HPV positivity in this study coincide with the known risk factors for cervical cancer found in the INSP/IARC case-control study, 13 namely being separated or divorced, being in a polygamous marriage and reporting of husband's extramarital sexual relationships. Nulliparity, which is a protective factor for ICC, was associated with being HPV positive in the present and in previous IARC HPV Prevalence Surveys, 18 but this association is likely to be confounded by unmeasured sexual behaviour.…”
Section: Short Reportsupporting
confidence: 74%
“…13 Exfoliated cervical cells of these ICC cases had been tested for HPV using the same detection and typing protocol. Both studies were approved by the IARC and Algerian National ethical review committees.…”
Section: Methodsmentioning
confidence: 99%
“…They included a series of case-control studies on ICC from eight developing countries with a broad range of rates of incidence of cervical cancer that were pooled for analysis. Regions covered include Morocco (Chaouki et al, 1998) and Algeria (Hammouda et al, 2005) in Africa; the Philippines (Ngelangel et al, 1998), Thailand (Chichareon et al, 1998) and Madras in Asia;and Brazil (Eluf-Neto et al, 1994), Colombia (Munoz et al, 1993), Paraguay (Rolon et al, 2000) and Peru (Eluf-Neto et al, 1994) in South America. Although Spain (Munoz et al, 1993) was part of the series of case -control studies, the sexual and reproductive behaviour of this population was heterogeneous to the other countries (late AFSI and low parity) and the study site was therefore excluded from this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The IARC multicentric case -control study Methods have been described earlier for the 11 individual studies carried out between 1985 and 1999 that have been included in this paper (Munoz et al, 1992;Eluf-Neto et al, 1994;Chaouki et al, 1998;Chichareon et al, 1998;Ngelangel et al, 1998;Rolon et al, 2000;Santos et al, 2001;Bayo et al, 2002;Franceschi et al, 2003;Hammouda et al, 2005). Briefly, eligible cases were residents in predefined study areas, or women attending reference hospitals with incident, histologically confirmed invasive cervical cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Control women were population based in the Spanish and Colombian studies (Munoz et al, 1992) and hospital or clinic based in other study areas. They were frequency matched by 5-year age group and did not include women admitted to hospital for cancers of the anogenital tract, breast and colon, smoking-related diseases (Munoz et al, 1992), or sexually transmitted infections (Hammouda et al, 2005). A total of 2390 control women were included between 1985 and 1999 ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%